The impact of overweight and obesity on the results of laparoscopic ventral hernia repair, including robot-assisted repair - a literature review - Ostojska, Magdalena; Kałuża, Izabela; Górska, Magdalena; Miazga, Małgorzata; Serkis, Barbara; Golemo, Jagna; Celichowska, Magdalena; Dziuba, Gabriela; Bentkowska, Zuzanna; Dębińska, Julia (Quality in Sport, 2024)
Obesity is the fifth leading cause of death worldwide. In turn, ventral hernias (including an inguinal hernias) are one of the most common cases in general surgery. Minimally invasive techniques (laparoscopic or robot-assisted procedures) are becoming more and more popular in ventral hernia treatment compared to open procedures. The aim of this study is to analyze the impact of body mass index (BMI) value on the efficacy and safety of laparoscopic ventral hernia repairs, including inguinal hernia repairs. Numerous studies evaluating this relationship are available. In most studies, There were also no statistically significant differences in the rate of intraoperative complications, the median operative time, the median length of hospital stay, the rate of postoperative pain, the surgical site infection, the rate of postoperative complications, the median time to recurrence, and the rate of early and late recurrences between groups with different BMI values. Moreover, studies proved that laparoscopic ventral hernia repair in obese patients is more effective compared to the open repair. The analysis revealed that high BMI values do not have a statistically significant impact on the outcomes of laparoscopic repair, including robot-assisted laparoscopic repair, in patients with ventral hernias. However, it should be noted that the analyzed studies often have limitations. For this reason, it is essential to conduct multicenter studies and perform long-term evaluations of patients.